Comparison of renal safety and efficacy of telbivudine, entecavir and tenofovir treatment in chronic hepatitis B patients: real world experience. (January 2016) - Tsai, M.-C.; Chen, C.-H.; Tseng, P.-L.; Hung, C.-H.; Chiu, K.-W.; Wang, J.-H.; Lu, S.-N.; Lee, C.-M.; Chang, K.-C.; Yen, Y.-H.; Lin, M.-T.; Chou, Y.-P.; et al.
Abstract: This study aims to assess the nephrotoxicity and efficacy of tenofovir disoproxil fumarate (tenofovir), telbivudine and entecavir. A retrospective study of 587 patients with chronic hepatitis B treated with tenofovir ( n = 170), telbivudine ( n = 184) and entecavir ( n = 233) for at least 1 year. Renal function and efficacy were assessed. The estimated glomerular filtration rate (eGFR) decreased significantly in the tenofovir group after a mean of 17 months treatment (from 92.2 to 85.6 mL/min/1.73 m 2, p < 0.001), but increased in the telbivudine group after a mean of 32 months of treatment (from 86.1 to 95 mL/min/1.73 m 2, p < 0.001). There was no significant change in eGFR in the entecavir group after a mean of 44 months. By multivariate analysis, pre-existing renal insufficiency (p = 0.003), tenofovir (p = 0.007) and diuretic treatment (p = 0.001) were independent predictors for renal function deterioration. Cumulative virological breakthrough was 0% in tenofovir after 2 years, 3.4% in entecavir after 7 years and 22.9% in telbivudine after 5 years. Liver cirrhosis (p = 0.008) and virological breakthrough (p = 0.040) were independently associated with increased risk of hepatocellular carcinoma development. Tenofovir may lead to deterioration in renal function as assessed by serial eGFR measurements. Although telbivudine appeared to be associated with an improvement in eGFR, it was associated with high rates of virological breakthrough, which was an independent risk factor for HCC development. With low rates of virological breakthrough and preservation of renal function, entecavir could be the best choice among these three agents.